cot ⎝ ⎛ n = 1 ∑ 4 cot − 1 ⎝ ⎛ 1 + k = 1 ∑ n 2 k ⎠ ⎞ ⎠ ⎞
If the above expression can be simplified into B A , where A and B are co-prime positive integers, find the value of A − B .
Bonus : Generalize this for any m ∈ N , such that T m = cot ( n = 1 ∑ m cot − 1 ( 1 + k = 1 ∑ n 2 k ) ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
∑ i = 1 n 2 i = 2 ( 2 n ( n + 1 ) ) = n ( n + 1 )
c o t − 1 ( n 2 + n + 1 ) = t a n − 1 ( 1 + n ( n + 1 ) 1 )
= t a n − 1 1 + n ( n + 1 ) ( n + 1 ) − ( n ) = t a n − 1 ( n + 1 ) − t a n − 1 n
Summation of this upto n=4 will give you t a n − 1 5 − t a n − 1 1
Ans:- t a n ( t a n − 1 5 − 4 π ) 1 = 1 + 5 ⋅ 1 5 − 1 1 = 4 6 = 2 3
Thus, the answer = 3 - 2 = 1.
Good one, why not try to reducing general term into a more simpler form consisting only of n
Problem Loading...
Note Loading...
Set Loading...
Let θ n = cot − 1 ( 1 + k = 1 ∑ n 2 k ) = cot − 1 ( n 2 + n + 1 ) and S m = n = 1 ∑ m θ n . Then we have:
\(\begin{array} {} m = 1 & \implies S_1 = \theta_1 = \cot^{-1} 3 & \implies S_{\color{blue}1} = \cot^{-1} \left(\dfrac {{\color{blue}1}+2}{\color{blue}1} \right) \\ m = 2 & \implies S_2 = \theta_1 + \theta_2 = \cot^{-1} 3 + \cot^{-1} 7 = \cot^{-1} \dfrac {3\times 7 - 1}{3 + 7} = \cot^{-1} 2 & \implies S_{\color{blue}2} = \cot^{-1} \left(\dfrac {{\color{blue}2}+2}{\color{blue}2} \right) \\ m = 3 & \implies S_3 = S_2 + \theta_3 = \cot^{-1} 2 + \cot^{-1} 13 = \cot^{-1} \dfrac {2\times 13 - 1}{2 + 13} = \cot^{-1} \dfrac 53 & \implies S_{\color{blue}3} = \cot^{-1} \left(\dfrac {{\color{blue}3}+2}{\color{blue}3} \right) \end{array} \)
This implies that S m = cot − 1 m m + 2 , which can be proven by induction as follows:
S m + 1 = S m + cot − 1 ( ( m + 1 ) 2 + m + 1 + 1 ) = cot − 1 m m + 2 + cot − 1 ( m 2 + 3 m + 3 ) = cot − 1 m m + 2 + m 2 + 3 m + 3 m m + 2 ( m 2 + 3 m + 3 ) − 1 = cot − 1 m 3 + 3 m 2 + 4 m + 2 m 3 + 5 m 2 + 8 m + 6 = cot − 1 ( m + 1 ) ( m 2 + 2 m 2 + 2 ) ( m + 3 ) ( m 2 + 2 m 2 + 2 ) = cot − 1 m + 1 m + 3 Proven
Therefore, X m = cot ( n = 1 ∑ m cot − 1 ( 1 + k = 1 ∑ n 2 k ) ) = cot S m = cot ( cot − 1 m m + 2 ) = m m + 2 . For m = 4 , X 4 = 4 4 + 2 = 2 3 . ⟹ A − B = 3 − 2 = 1 .